Can Propofol Be Used to Assess the Presence of the Rectoanal Inhibitory Reflex During Anorectal Manometry Studies?. Issue 1 (12th August 2021) - Arbizu, Ricardo A.; Amicangelo, Maureen; Rodriguez, Leonel; Nurko, Samuel
ABSTRACT: Objectives: To study changes in intra-anal pressure (IAP) and characteristics of the rectoanal inhibitory reflex (RAIR) during anorectal manometry (ARM) in patients undergoing anesthesia induction with propofol. Methods: Prospective study in which ARM was performed at baseline while patients were awake and repeated after propofol-induced anesthesia. We studied IAP and the presence and characteristics of the RAIR before and after propofol. Results: A total of 27 patients were included (63% male; 9.2 years). Three patients had obstructive symptoms after Hirschsprung disease repair (HSCR), and 24 had intractable constipation. At baseline, the RAIR was present on 21 of 27 patients and absent on 6 of 27. Of the six patients with an absent RAIR, it remained absent in four of six (three known HSCR, and one new diagnosis of IAS achalasia), and two of six had a normal RAIR during propofol. Therefore, RAIR was present in all patients with constipation. The mean resting IAP was significantly lower after propofol. The percentage of IAS relaxation after lower balloon volume inflations was significantly higher during propofol ( P < 0.05). No difference was observed over the latency time or the total relaxation time after propofol. Conclusions: Propofol can be used to assess the presence of the RAIR during ARM in children who are uncooperative and undergoing other procedures under anesthesia. On the other hand, propofol significantly reduces the resting IAP and increases the percentage of internal anal sphincter relaxation after balloon distention. These findings may impact the interpretation to decide if an intervention is needed, or if there is a possible spinal neuropathy.